Sensitivity of Dairy Cattle Development in Pujon District, Malang Regency - Erlin Sulistyorini; Agnes Pudjiastuti; Budi Prihatminingtyas (International Journal of Management, Accounting and Economics, 2019)
Milk that is produced by dairy cows was currently not able to meet the needs of Indonesian, so it is necessary to develop small-scale dairy cattle business. This study aims to analyze feasibility and sensitivity of dairy cattle business development in the District of Pujon, Malang Regency. Research location was determined by purposively under consideration that this area was a center of dairy cattle business. Business feasibility was measured by commonly used parameters and sensitivity to changes in milk prices and feed prices. The results showed that dairy cattle business in the District of Pujon Malang Regency was profitable in terms of financial aspects so it was feasible to be developed. Sensitivity analysis shows that the dairy cattle business is still feasible to be developed even though feed price increases by 5% and milk price decreases by 5%.